Why SMEs Should Consider Adopting Cloud ERP: A Literature Review - Suppiah, Yogeswari; Hassan, Marina (Proceedings of the Informatics Conference, 2020)
Abstract – Technology is ever changing. On-premiseERP has been adopted by industries almost two andhalf decades ago. Nowadays, cloud computing has takenover the technology era. Cloud computing plays a vitalrole in offering an organizations with a pool of thirdparty hosting of IT resources applications and servicesvirtually through the web. Cloud ERP also known asSaaS( Software-As-Service) ERP. Current studies showthat there are many large organizations have beenadopting cloud ERP recently. They have observed thebenefits and opportunities offered by cloud computing.But SMEs are resistant to adopt to this new technologyfor various possible reasons mainly high cost ofimplementation. This paper aims to provide a detailedoverview on the opportunities, benefits and advantagesof cloud ERP. This paper would be useful for futureadopters and decision makers of cloud ERP in SMEs.